The impact of natural science contextual teaching through project method to students’ achievement in MTsN Miri Sragen - Anik Sunarsih; Sukarmin Sukarmin; Widha Sunarno (International Journal of Science and Applied Science: Conference Series, 2017)
This study aims to describe the science learning skills among students’ who follow contextual learning through project method with experiment method. The population of this research is the students’ of class VII MTS Negeri Miri Kab. Sragen on the teaching period of 2016/2017. Cluster random sampling technique is used as sample. This research was designed using contextual teaching through project method as an independent variable. The results of this Improvement show that there is a difference in the achievement of students' learning skill that follows contextual learning through the project method with the experimental method with Fobs = 8,83 and significant number 4,04 (p <0,05). Based on these findings contextual learning through the project is one of the learning methods that provide a positive influence on improving the achievement of science learning skills. This ain increase, because CTL is can help students’ understand the material by relating the problems that exist. Project methods are used by students’ in solving problems.